Glucose and glutamine handling in the Sertoli cells of transgenic rats overexpressing regucalcin: plasticity towards lactate production - Mateus, Inês (2018)
Sertoli cells (SCs) possess the unparalleled ability to provide the germ line with growth factors and nutrients. Although SCs can oxidize amino acids, e.g., glutamine, they mostly metabolize glucose, producing high amounts of lactate, the germ cells preferential substrate. Regucalcin (RGN) is a calcium-binding protein that has been indicated as a regulator of cell metabolism. In this study, we investigated glucose and glutamine handling in the SCs of transgenic rats overexpressing RGN (Tg-RGN) comparatively with wild-type (Wt) littermates. Primary SCs isolated from adult Tg-RGN animals and maintained in culture for 24 hours, produced and exported more lactate, despite consuming less glucose. These observations were underpinned by increased expression of alanine transaminase, and augmented glutamine consumption, suggesting that alternative routes are contributing to the enhanced lactate production in the SCs of Tg-RGN rats. Moreover, lactate seems to be used by germ cells, with diminished apoptosis being detected in the seminiferous tubules of Tg-RGN animals cultured ex vivo. The obtained results showed a distinct metabolism in the SCs of Wt and Tg-RGN rats widening the roles assigned to RGN in spermatogenesis. These findings also highlighted the plasticity of SCs metabolism, a feature that would be exploited in the context of male infertility.